1971
DOI: 10.1073/pnas.68.11.2712
|View full text |Cite
|
Sign up to set email alerts
|

The Sequential Unfolding of Ribonuclease A: Detection of a Fast Initial Phase in the Kinetics of Unfolding

Abstract: Temperature-jump studies have been used to detect a rapid reaction in the thermal unfolding of ribonuclease A (RNase A). The fast reaction occurs over a wide range of pH, and the results of a detailed study at pH 1.3 are reported here. Although its amplitude is small, the reaction is easily measurable over the entire temperature range of thermal unfolding. It occurs in the millisecond time range, and is faster by 3-4 orders of magnitude than the slow unfolding reaction studied previously. Unfolding is measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
2

Year Published

1972
1972
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 16 publications
2
40
2
Order By: Relevance
“…The thermal denaturation in particular has been studied by a wide variety of techniques including circular dichroism (5), electron paramagnetic resonance of covalently bound spin labels (6), the action of proteolytic enzymes on RNase A during the course of denaturation (7), thermocalorimetry (8), ultraviolet difference spectroscopy (9), and temperature-jump and pHjump kinetic experiments (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…The thermal denaturation in particular has been studied by a wide variety of techniques including circular dichroism (5), electron paramagnetic resonance of covalently bound spin labels (6), the action of proteolytic enzymes on RNase A during the course of denaturation (7), thermocalorimetry (8), ultraviolet difference spectroscopy (9), and temperature-jump and pHjump kinetic experiments (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…We could look for unfolding intermediates formed between 10 −5 and 10 −1 s. Tian's 1971 T-jump experiments on RNase A unfolding showed that at least one intermediate is present (81). Tian next found a similar result with chymotrypsinogen A (80), which, like RNase A, was considered a paradigm for two-state protein folding.…”
Section: Protein Folding Intermediates and Proline Isomerizationmentioning
confidence: 51%
“…On these pathways, the protein molecule passes through well-defined partiallystructured intermediate states. Based on this view, numerous experiments and simulations were conducted to test the existence of transient folding intermediates [4,5]. It was expected that the determination of the structures and population of folding intermediates could help elucidate protein folding mechanisms.…”
Section: Studying Protein Foldingmentioning
confidence: 99%